Development of artificial intelligence as a science - Abdujabborov Madaminjon (Global Scientific Publishing, 2023)
This article covers the development of artificial intelligence (AI) as a science and its historical progression from ancient times to the present. It explores the possibilities of artificial intelligence and highlights the contributions of scientists, both in our country and abroad, who have played a significant role in its development
Keywords: Informatics; Artificial intelligence; computer; robot